O modelo de Schrödinger não linear com um defeito integrável - Silva, Douglas Rodrigues [UNESP] (2015)
The theory of integrable defects in 1+1 ﬁeld theory, was introduced by the school of York [16, 17, 22], employing B¨acklund transformation in order to describe the defect. In this dissertation we have studied the nonlinear Schrödinger model in the presence of an integrable defect. We study both, the discrete model [29] as the continuous model within the lagrangian [23] andr matrix [7] formalisms. Also we built the hamiltonian formalism for nonlinear Schrödinger model in the presence of an integrable defect. We discuss and relate the lagrangian, hamiltonian and r matrix formalisms